2015
DOI: 10.1080/09593330.2015.1063707
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adsorbents for H2S and D4 removal for biogas conversion in a solid oxide fuel cell

Abstract: Biogas contains trace compounds detrimental for solid oxide fuel cell (SOFC) application, especially sulphur-containing compounds and volatile organic silicon compounds (VOSiCs). It is therefore necessary to remove these impurities from the biogas for fuelling an SOFC. In this paper, dynamic lab-scale adsorption tests were performed on synthetic polluted gas to evaluate the performance of a polishing treatment to remove hydrogen sulphide (H2S - sulphur compound) and octamethylcyclotetrasiloxane (D4 - VOSiC). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 47 publications
0
8
1
Order By: Relevance
“…Ducom et al (2013) showed how fly ash from biomass was able to remove some trace compounds from the biogas [40]. Fly ash from wood waste and char have a lower removal capacity for the desulphurisation of biogas compared to commercially activated carbons [39,[41][42][43][44]. The waste materials adopted for the purpose of cleaning biogas require more research, especially on the improvement of their physical characteristics, such as microporous volume and specific surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Ducom et al (2013) showed how fly ash from biomass was able to remove some trace compounds from the biogas [40]. Fly ash from wood waste and char have a lower removal capacity for the desulphurisation of biogas compared to commercially activated carbons [39,[41][42][43][44]. The waste materials adopted for the purpose of cleaning biogas require more research, especially on the improvement of their physical characteristics, such as microporous volume and specific surface area.…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of zeolites for removing VMSs from biogas has been confirmed by numerous studies, e.g., [31,39,40]. Owing to their high thermal resistance they are also suitable for repeated thermal regeneration [25].…”
Section: Adsorption Of Vmss Using Zeolitesmentioning
confidence: 92%
“…Hydrogen sulfides and halogens are adsorbed on Ni/YSZ active surface inhibiting the catalytic reactions [688]. H 2 S and HCl are removed by adsorption in materials, such as activated carbon, metal oxides (ZnO, MnO, CuO), silica gel and zeolites [689], or chemical absorption in water [690]. The hydrogen sulfide solubility is improved by alkaline compounds or by H 2 S catalytic oxidation [690].…”
Section: Fuel Cells Gas Qualitymentioning
confidence: 99%